Assessment Of Water Quality In High-Rise Residential Building - Faizal, Muhammad Ikhlas Saufi Mohd (Universiti Sains Malaysia, 2019)
This research has two main objectives which are to monitor the water quality of selected high-rise residential building in Seberang Perai, Penang and compare the result with Malaysian drinking water quality standard and to estimate chlorine availability and its water ages at the user’s end using EPANET 2.0 modelling software. This study was carried out to examine the drinking water quality of high-rise residential buildings distribution network in Universiti Sains Malaysia by collecting samples from 2 different locations (Desasiswa Tekun and Utama). The aim is to determine the potential relationship between the water age stored in the tanks with the chlorine in the distribution network and test weather can the EPANET 2.0 be use to estimate or predict water quality in small building. The residual chlorine is tested in situ immediately while pH, turbidity and colour are brought back to school of Civil Engineering’s laboratory for the test. The water age and chlorine availability were estimated by using water distribution network software modelling EPANET 2.0. The result of this study have shown that assessment of drinking water quality at both USM high-rise residential building and estimation by using EPANET 2.0 water distribution simulation modelling software, this study elucidated that the quality of water supplied are fulfilled the Malaysia drinking water quality standard which is pH of water is within 6.5-9.0, turbidity contain are less than 5 NTU, colour of water is less than 15 TCU and free residual chlorine contain are within 0.2-0.5 mg/l. The value of chlorine contains predicted by the EPANET 2.0 was lies within the range of result in-situ tested